STAAD Based G+2 Single-Column Residential Analysis - Baidya, Biswajit (Journal of Progress in Civil Engineering, 2024)
The principle cause of this study is to layout a whole building relaxation on a single column. The rapid increase in population and scarcity of land tends to the development of construction technology and high- rise commercial structures. The building plays a vital role in improving various activities in the late world. The Aim of present study “Analysis and design of high rise building by staad pro is to define proper technique for creating Geometry, cross sections for column and beam etc, developing specification and supports conditions, types of Loads and load combinations. In this study a 30- storey high rise structure is analyzed for seismic and wind load combination using staad pro and comparison is drawn. Currently, there are four mosques on Java Island recognized as Saka Tunggal Mosques, which employ a single wooden column as the main column, placed at the center of the prayer hall to support the roof. This unique structural system, when compared to the traditional four-column system, is remarkable even if its style is exceptional for mosques on Java Island. This study aims to provide scientific data and promote the local government's understanding about the importance of the Saka Tunggal Mosques by focusing on the one in Banyumas, which is placed at a cultural heritage site, founded in 1871. The rapid increase in population and scarcity of land tends to the development of construction technology and high-rise commercial structures. Building plays a vital role for improving the various activities. In the late world, prompt to action of peoples from one place to another is of great extent mainly for earnings. In building more facilities like financing section, computer section, administration section, design section and drawing section are provided. The aim of the project is to analyse and design of multi-storey building resting on the single column by using different code provisions. A lay out plan of the proposed building is drawn by using AUTO CADD. The structure consists of ground floor plus five floors, each floor having the one house. Staircase must be provided separately. The planning is done as per Indian standard code provisions. The building frames are analyzed using the various text books. Using this so many standard books analysis of bending moment, shear force, deflection, end moments and foundation reactions are calculated. Detailed structural drawings for critical and typical R.C.C. members are also drawn. Recent studies regarding progressive collapse resistance of buildings considered only single critical column removal scenario. However, limited investigations have been conducted so far to assess multi-column removal scenarios. Hence this study is made to compare progressive collapse resistance of a multi-story building under both single and multi-column removal scenarios. An eight-storey reinforced concrete building was analyzed by using linear static analysis procedure and DCR values of the members are calculated to investigate the potential of progressive collapse as per GSA guideline.